2022
DOI: 10.1007/s11192-021-04200-w
|View full text |Cite
|
Sign up to set email alerts
|

An evolving international research collaboration network: spatial and thematic developments in co-authored higher education research, 1998–2018

Abstract: Co-authored research articles in the disciplinarily heterogeneous field of higher education have dramatically increased in this century. As in other fields, rising international co-authorships reflect evolving international collaboration networks. We examine higher education research over two decades, applying automated bibliometric topic identification and social network analysis of 9067 papers in 13 core higher education journals (1998–2018). Remarkable expansion in the volume of papers and co-authorships h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 79 publications
(114 reference statements)
2
15
1
Order By: Relevance
“…Other increments in terms of collaborating countries worth noting across Europe include Norway (from 1 country in the period 1972–2009 to 11 countries in the period 2016–2021), Finland (from 3 to 13 countries in the same periods), Denmark (from 1 to 9 countries), Italy (from 0 to 10 countries), Germany (from 2 to 14 countries), and Belgium (from 2 to 11 countries). These patterns confirm a trend of rising international collaborations in higher education research (Akbaritabar & Barbato, 2021 ; Avdeev, 2021 ; Fu et al, 2022 ; Vlegels and Huisman, 2021 ).…”
Section: International Collaborationsupporting
confidence: 64%
See 4 more Smart Citations
“…Other increments in terms of collaborating countries worth noting across Europe include Norway (from 1 country in the period 1972–2009 to 11 countries in the period 2016–2021), Finland (from 3 to 13 countries in the same periods), Denmark (from 1 to 9 countries), Italy (from 0 to 10 countries), Germany (from 2 to 14 countries), and Belgium (from 2 to 11 countries). These patterns confirm a trend of rising international collaborations in higher education research (Akbaritabar & Barbato, 2021 ; Avdeev, 2021 ; Fu et al, 2022 ; Vlegels and Huisman, 2021 ).…”
Section: International Collaborationsupporting
confidence: 64%
“…Interrelatedly, in examining collaborative patterns in Studies in Higher Education , Calma and Davies ( 2015 ) found that more articles were published by single authors in the 1980s but pointed to ‘a trend away from solo- to multiple-author research in recent decades’ (2015:10). Other studies have also confirmed a trend to collaborate more in publications in higher education research (Akbaritabar & Barbato, 2021 ; Avdeev, 2021 ; Fu et al, 2022 ; Vlegels & Huisman, 2021 ).
Fig.
…”
Section: Articles’ Authorshipmentioning
confidence: 73%
See 3 more Smart Citations